Homogeneous Cobalt/Vanadium Complexes as Precursors for Functionalized Mixed Oxides in Visible‐Light‐Driven Water Oxidation. Issue 20 (30th September 2016) - Pavliuk, Mariia V.; Mijangos, Edgar; Makhankova, Valeriya G.; Kokozay, Vladimir N.; Pullen, Sonja; Liu, Jia; Zhu, Jiefang; Styring, Stenbjörn; Thapper, Anders
Abstract: The heterometallic complexes (NH4 )2 [Co(H2 O)6 ]2 [V10 O28 ]⋅ 4 H2 O (1 ) and (NH4 )2 [Co(H2 O)5 (β‐HAla)]2 [V10 O28 ]⋅ 4 H2 O (2 ) have been synthesized and used for the preparation of mixed oxides as catalysts for water oxidation. Thermal decomposition of1 and2 at relatively low temperatures (<500 °C) leads to the formation of the solid mixed oxides CoV2 O6 /V2 O5 (3 ) and Co2 V2 O7 /V2 O5 (4 ). The complexes (1, 2 ) and heterogeneous materials (3, 4 ) act as catalysts for photoinduced water oxidation. A modification of the thermal decomposition procedure allowed the deposition of mixed metal oxides (MMO) on a mesoporous TiO2 film. The electrodes containing Co/V MMOs in TiO2 films were used for electrocatalytic water oxidation and showed good stability and sustained anodic currents of about 5 mA cm −2 at 1.72 V versus relative hydrogen electrode (RHE). This method of functionalizing TiO2 films with MMOs at relatively low temperatures (<500 °C) can be used to produce other oxides with different functionality for applications in, for example, artificial photosynthesis. Abstract : When one metal isn't enough : Two cobalt/vanadium heterometallic complexes and mixed metal oxides (MMOs) prepared from the complexes at mild temperatures are used as catalysts for water oxidation. Additionally, the MMOs can be prepared on TiO2 films and used for electrochemical water oxidation. The electrodes prepared in this way sustain high current densities at relatively low overpotentials.